Особливості морфології та cтресостійкості рослин Stevia rebaudiana (Вert.) Bertoni залежно від форм та умов вирощування - Левчик, Н.Я.; Рахметов, Д.Б.; Левон, В.Ф.; Любінська, А.В.; Сапсай, В.І.; Климчук, Д.О. (Фактори експериментальної еволюції організмів, 2016)
Aim. Study of leaf surface morphology microstructure peculiarities of plants Stevia rebaudiana, character of waterholding capacity dependent on growing conditions (open soil and in vitro) and influence on adaptation abilities of economically valuable introduced plants. Methods. Microexamination of leaf surface on microscope GAOL, GSM-6060 LA. Evaluation of tissue water-holding ability, qualitative and quantitative analysis of amino acids. Results. In vitro conditions Stevia rebaudiana 3Т plant shows the biggest size of stomas (long 43.29±1.12 µm, wide 31.17±2.36 µm) and the smallest quantity of them (110.83±11.45 pieces/mm2 ). Stevia rebaudiana St5 plant shows the smallest size of stomas (long 18.96±0.59 µm, wide 11.85±1.13 µm) and the biggest quantity of them (224.2±25.65 pieces/mm2 ). After the transference into the cultural conditions, the stomas’ size of these plants’ form increase on 37% in long and 44% in wide and number of stomas on abaxial surface increase on 10%. It was found that plants Stevia rebaudiana from open soil, regardless of forms, during drought to lose humidity gradually and, as a result, 20–25% less then plants cultivated in agar medium. Stevia rebaudiana R100 has the biggest water-holding ability and the highest level of proline, regardless of cultivations conditions, Stevia rebaudiana 3T – the smallest one. Conclusions. Cultivation conditions of Stevia rebaudiana plants have direct impact on peculiarities of leaf surface morphology structure, by increasing size and quantity of stomas. Stevia rebaudiana plants in introduction conditions have low level of drought-resistance. Open soil plants are more drought-resistance, then plants cultivated in vitro. Stevia rebaudiana R100 plants have the highest level of drought- and stress-resistance among investigated forms, Stevia rebaudiana 3T – the smallest one. Keywords: stomas, Stevia rebaudiana, water-holding ability, proline, drought-resistance.